2020
DOI: 10.24057/2071-9388-2019-123
|View full text |Cite
|
Sign up to set email alerts
|

Green infrastructure indicators for urban planning: applying the integrated approach for Russian largest cities

Abstract: Modern approaches to urban planning assume the dualistic nature of urban green infrastructure (GI). On the one hand, green infrastructure is as an integrated network of natural and semi-natural areas, featuring a delivery of various benefits to humans. On the other hand, GI is multifunctional and provides the residents by complex of ecosystem services to be user-oriented. Most official reports and programs use common indicators that do not characterize distribution, dynamics or state of GI. In our research, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Both in Serbia and Italy, there are no mandatory planning tools for the design and management of GI, and they are now a part of traditional land use plans [69]. Moreover, the lack of financial resources allocated towards the development of "green standards" presents a challenge for the majority of the public administrations in Serbia as well as in other countries [69][70][71]. Therefore, it is proposed to abolish the monopolies held by public utility companies for green spaces to foster competition, deliver higher-quality services at more-affordable rates, and establish a cohesive management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Both in Serbia and Italy, there are no mandatory planning tools for the design and management of GI, and they are now a part of traditional land use plans [69]. Moreover, the lack of financial resources allocated towards the development of "green standards" presents a challenge for the majority of the public administrations in Serbia as well as in other countries [69][70][71]. Therefore, it is proposed to abolish the monopolies held by public utility companies for green spaces to foster competition, deliver higher-quality services at more-affordable rates, and establish a cohesive management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Estimating the number of green stands involves rationing these. The London Department for Communities and Local Government has set a standard of 40% green infrastructure as a percentage of the city's total land [58,61]. However, the notion of green infrastructure goes beyond green spaces.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization recommends the minimum availability of green space per inhabitant to −9 m 2 per person and the ideal −50 m 2 per person [9]. Each city resident should have a green space within a 15 min walk [60,61]. The 15 min walking distance to green areas has also been defined as an indicator of urban environmental quality at the European level.…”
Section: Discussionmentioning
confidence: 99%
“…The above three measures can be evaluated on the scale of pedestrian movement or on the whole system by using the DepthmapX open-source software. Some studies suggested that five, ten, or fifteen minutes of walk (equivalent to the distance of 400, 800, and 1200 m respectively) are comfortable walking times to reach services and facilities (Klimanova & Illarionova, 2020). This research used an average value of 800 m to perform the analysis on the pedestrian movement scale.…”
Section: Phase 3: Assessment Of Uqol Index For Each Land Parcelmentioning
confidence: 99%